Effectiveness of sodium hypochlorite and peracetic acid for spoilage-causing molds on sweet potato slices - Hosotani, Yukie; Nakamura, Nobutaka; Kito, Hideki; Inatsu, Yasuhiro (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
In the present study, the effectiveness of sterilization of peracetic acid (PA) solution and sodium hypochlorite (SH) solution for several fungi (Penicillium sp., Cladosporium sp., and Fusarium sp.) attached on the cut surface of sweet potato (Ipomoea batatas) was evaluated. The mixture of each strain isolated from rotten sweet potatoes was inoculated on the cut surface of presterilized sweet potato blocks. Further, each inoculated cut potato was washed with water, 200 mg/L SH, a mixture of SH, and 100 mM acetic acid (SH+AA), or 20–80 mg/L PA for 5 min at room temperature. Comparing with the untreated ones (4.2–5.1 log CFU/mL), the 80 mg/L PA washing could reduce 2.2, 2.2, and 2.0 log CFU/mL of Penicillium, Fusarium, and Cladosporium species, respectively. The increasing concentration of PA resulted in an increase the fungicidal efficiency. The use of 80 mg/L PA solution was suggested to be more highly effective than the one of (pH controlled) SH solution to control the spoilage fungi on cut sweet potato.